자기주장성과 외모만족이 심리적 안녕감에 미치는 영향 - 박혜원; Hea Won Park; 정명선; Myung Sun Chung (The Research Journal of the Costume Culture, 2014)
This study aimed to investigates the effects of self-assertiveness and appearance satisfaction on psychological well-being (personal growth, purpose in life, self acceptance, environmental mastery, autonomy and interpersonal relations), and find out if there exists any causal relationship among each variable in the process. For data collection, a questionnaire was administrated from April 23 to May 13, 2012 in the city of Gwangju, Korea. The subjects were women in their twenties and thirties. 359 women responded to it. The results were as follows. First, overall self assertiveness had positive effects on appearance satisfaction which, in turn, turned out to have overall positive effects. Second, the overall effects of self assertiveness on psychological well-being turned out to have positive effects. Third, overall appearance satisfaction had positive effects on psychological well being. Forth, the effects that self assertiveness had on psychological well-being mediated appearance satisfaction and appeared to be partly insignificant. The implications and the direction of this research should be discussed in the future study so that it can improve personal psychological well-being by finding out other variables aside from self assertiveness, appearance satisfaction.